Effect of acute nitrite infusion on contractile economy and metabolism in isolated skeletal muscle in situ during hypoxia. (14th June 2020) - Porcelli, Simone; Rasica, Letizia; Ferguson, Brian S.; Kavazis, Andreas N.; McDonald, James; Hogan, Michael C.; Grassi, Bruno; Gladden, L. Bruce
Abstract : Key points: Increased plasma nitrite concentrations may have beneficial effects on skeletal muscle function. The physiological basis explaining these observations has not been clearly defined and it may involve positive effects on muscle contraction force, microvascular O2 delivery and skeletal muscle oxidative metabolism. In the isolated canine gastrocnemius model, we evaluated the effects of acute nitrite infusion on muscle force and skeletal muscle oxidative metabolism. Under hypoxic conditions, but in the presence of normal convective O2 delivery, an elevated plasma nitrite concentration affects neither muscle force, nor muscle contractile economy. In accordance with previous results suggesting limited or no effects of nitrate/nitrite administrations in highly oxidative and highly perfused muscle, our data suggest that neither mitochondrial respiration, nor muscle force generation are affected by acute increased concentrations of NO precursors in hypoxia. Abstract: Contrasting findings have been reported concerning the effects of augmented nitric oxide (NO) on skeletal muscle force production and oxygen consumption ( V ̇ O 2 ). The present study examined skeletal muscle mitochondrial respiration and contractile economy in an isolated muscle preparation during hypoxia (but normal convective O2 delivery) with nitrite infusion. Isolated canine gastrocnemius muscles in situ ( n  = 8) were studied during 3 min of electrically stimulated isometric tetanic contractions corresponding to ∼35% of V ̇ O 2 peak . During contractions, sodium nitrite (NITRITE) or sodium chloride (SALINE) was infused into the popliteal artery. V ̇ O 2 was calculated from the Fick principle. Experiments were carried out in hypoxia ( F I O 2  = 0.12), whereas convective O2 delivery was maintained at normal levels under both conditions by pump‐driven blood flow ( Q ̇ ). Muscle biopsies were taken and mitochondrial respiration was evaluated by respirometry. Nitrite infusion significantly increased both nitrite and nitrate concentrations in plasma. No differences in force were observed between conditions. V ̇ O 2 was not significantly different between NITRITE (6.1 ± 1.8 mL 100 g −1  min −1 ) and SALINE (6.2 ± 1.8 mL 100 g −1  min −1 ), even after being 'normalized' per unit of developed force (muscle contractile economy). No differences between conditions were found for maximal ADP‐stimulated mitochondrial respiration (both for complex I and complex II), leak respiration and oxidative phosphorylation coupling. In conclusion, in the absence of changes in convective O2 delivery, muscle force, muscle contractile economy and mitochondrial respiration were not affected by acute infusion of nitrite. The previously reported positive effects of elevated plasma nitrite concentrations are presumably mediated by the increased microvascular O2 availability. Key points: Increased plasma nitrite concentrations may have beneficial effects on skeletal muscle function. The physiological basis explaining these observations has not been clearly defined and it may involve positive effects on muscle contraction force, microvascular O2 delivery and skeletal muscle oxidative metabolism. In the isolated canine gastrocnemius model, we evaluated the effects of acute nitrite infusion on muscle force and skeletal muscle oxidative metabolism. Under hypoxic conditions, but in the presence of normal convective O2 delivery, an elevated plasma nitrite concentration affects neither muscle force, nor muscle contractile economy. In accordance with previous results suggesting limited or no effects of nitrate/nitrite administrations in highly oxidative and highly perfused muscle, our data suggest that neither mitochondrial respiration, nor muscle force generation are affected by acute increased concentrations of NO precursors in hypoxia.